Research on decision-making behavior of power suppliers considering multi-market integration and network security - Qiao, Jiyang; Li, Min; Liu, Jichun; Lu, Yi; Sun, Yi; Liu, Yang; Yang, Yuyan (Frontiers in Energy Research, 2023)
The construction of a power system including renewable energy has become the direction of development for the power industry as a result of the “carbon peaking and carbon neutrality” targets. Yet because the electricity market (EM), carbon market (CM), and green certificate market (GCM) have traditionally operated independently, with little interaction among them. To explore the interaction and correlation among the three markets, this paper analyzes the trading patterns and mutual influencing factors of the EM, CM and GCM and proposes the optimal decision-making model of “carbon-electricity-certificate” integration of multiple markets based on the decision-making behavior of power producers in each market. Finally, the golden jackal optimization algorithm (GJO) is used to solve the problem under the condition of network security. The simulation results show that the integration of multiple markets is more conducive to promoting the consumption of renewable energy source (RES), and also verify the feasibility and effectiveness of GJO in solving the optimal decision-making problem of power producers in EM.